2020
DOI: 10.4014/jmb.1908.08056
|View full text |Cite
|
Sign up to set email alerts
|

Brucella melitensis omp31 Mutant Is Attenuated and Confers Protection Against Virulent Brucella melitensis Challenge in BALB/c Mice

Abstract: For control of brucellosis in small ruminants, attenuated B. melitensis Rev1 is used but it can be virulent for animals and human. Based on these aspects, it is essential to identify potential immunogens to avoid these problems in prevention of brucellosis. The majority of OMPs in the Omp25/31 family have been studied because these proteins are relevant in maintaining the integrity of the outer membrane but their implication in the virulence of the different species of this genus is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…At present, some experiments have shown that Omp10, Omp19, Omp25, and Omp31 are involved in Brucella virulence (11)(12)(13). The Brucella Omp19, Omp25, and Omp31 mutant were attenuated in cellular models and in mice, indicating that Omp19 and Omp25 were important for bacterial survival in vitro and in vivo (11,(14)(15)(16)(17). Furthermore, Omp25 and Omp31 disrupt the immune response by regulating the secretion of tumor necrosis factor alpha (TNF-α) expression and apoptosis in porcine and murine macrophages infected models (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…At present, some experiments have shown that Omp10, Omp19, Omp25, and Omp31 are involved in Brucella virulence (11)(12)(13). The Brucella Omp19, Omp25, and Omp31 mutant were attenuated in cellular models and in mice, indicating that Omp19 and Omp25 were important for bacterial survival in vitro and in vivo (11,(14)(15)(16)(17). Furthermore, Omp25 and Omp31 disrupt the immune response by regulating the secretion of tumor necrosis factor alpha (TNF-α) expression and apoptosis in porcine and murine macrophages infected models (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, seeking for new PLOS NEGLECTED TROPICAL DISEASES candidate antigen to replace LPS is of great significance for developing brucellosis detecting kits which can be easily produced and available to all users. According to literatures, many Brucella OMPs manifested strong capacity in arousing humoral immune response [14][15][16], and some of these proteins have also been used for development of subunit vaccine against brucellosis [17,18]. In our previous study, some Brucella OMPs showed quite satisfactory result in diagnosing brucellosis, basically comparable to LPS antigen [7].…”
Section: Discussionmentioning
confidence: 90%
“…PG and lipoteichoic acids in human monocytes also have been stated to induce the secretion of this cytokine [ 50 ]. Although the monovalent lysate of E. faecalis did not show a stimulatory effect on either of the two cell types used, the result confirms that bacterial structures vary between genera and species [ 52 , 53 ], which supports the relevance of using immunogens with epitopes expressed by the different microorganisms [ 24 , 30 , 32 ]. In addition, with regard to LPS, it has been reported that in conjunction with bacterial flagellin, it induces TNF-α production [ 54 ].…”
Section: Discussionmentioning
confidence: 74%
“…It is important to note that outer membrane proteins are considered important epitopes for the development of diagnostic systems and mainly vaccines, because of their ability to stimulate the immune response [ 29 , 31 , 32 , 33 ]. The protein composition of the UNAM-HIMFG lysate is very diverse ( Figure 1 A,B); to know if some of these proteins were immunogenic, their reactivity was evaluated by WB assays.…”
Section: Discussionmentioning
confidence: 99%